Selenium (Se) improves drought tolerance in crop plants – a myth or fact?. (26th June 2015) - Ahmad, Rashid; Waraich, Ejaz Ahmad; Nawaz, Fahim; Ashraf, Muhammad Y; Khalid, Muhammad
Abstract: Climate change has emerged as one of the most complex challenges of the 21st century and has become an area of interest in the past few decades. Many countries of the world have become extremely vulnerable to the impacts of climate change. The scarcity of water is a serious concern for food security of these countries and climate change has aggravated the risks of extreme events like drought. Oxidative stress, caused by a variety of active oxygen species formed under drought stress, damages many cellular constituents, such as carbohydrates, lipids, nucleic acids and proteins, which ultimately reduces plant growth, respiration and photosynthesis. Se has become an element of interest to many biologists owing to its physiological and toxicological importance. It plays a beneficial role in plants by enhancing growth, reducing damage caused by oxidative stress, enhancing chlorophyll content under light stress, stimulating senesce to produce antioxidants and improving plant tolerance to drought stress by regulating water status. Researchers have adopted different strategies to evaluate the role of selenium in plants under drought stress. Some of the relevant work available regarding the role of Se in alleviating adverse effect of drought stress is discussed in this paper. © 2015 Society of Chemical Industry